Ancient Eastern Scholars on State Governance (Eurasian Research Bulletin, 2022)
From a historical and theoretical point of view, the article analyzes the views of the thinkers of the ancient East on public administration, the structure of society, forms and methods of public administration, based on the study of historical sources.